2003
DOI: 10.1038/ng1157
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of antisense RNA leading to gene silencing and methylation as a novel cause of human genetic disease

Abstract: Nearly all human genetic disorders result from a limited repertoire of mutations in an associated gene or its regulatory elements. We recently described an individual with an inherited form of anemia (alpha-thalassemia) who has a deletion that results in a truncated, widely expressed gene (LUC7L) becoming juxtaposed to a structurally normal alpha-globin gene (HBA2). Although it retains all of its local and remote cis-regulatory elements, expression of HBA2 is silenced and its CpG island becomes completely meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
353
1
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 493 publications
(368 citation statements)
references
References 36 publications
7
353
1
7
Order By: Relevance
“…Second, antisense mRNAs were suggested to promote the methylation of sense mRNA promoters. And third, the formation of double-stranded RNA hybrids may interfere with further mRNA processing (Wutz et al, 1997;Lai, 2002;Prescott and Proudfoot, 2002;Tufarelli et al, 2003;Lavorgna et al, 2004;Crampton et al, 2006). These models are not mutually exclusive, and more than one of them may apply to the situation of p53 and WRAP53.…”
Section: Discussionmentioning
confidence: 99%
“…Second, antisense mRNAs were suggested to promote the methylation of sense mRNA promoters. And third, the formation of double-stranded RNA hybrids may interfere with further mRNA processing (Wutz et al, 1997;Lai, 2002;Prescott and Proudfoot, 2002;Tufarelli et al, 2003;Lavorgna et al, 2004;Crampton et al, 2006). These models are not mutually exclusive, and more than one of them may apply to the situation of p53 and WRAP53.…”
Section: Discussionmentioning
confidence: 99%
“…To date, antisense transcripts have been observed for up to 75% of the mammalian transcriptome in data sets generated by both sequence-based and hybridization-based methods (Katayama et al 2005). Given the high prevalence of antisense transcription in the mammalian genome, and the link between antisense transcripts and disease (Tufarelli et al 2003;Reis et al 2004), Tag-seq was well suited to the study of cancer-relevant gene expression in the context of the CGAP project. We found known and novel S-AS gene pairs for which the ratio of expression changed significantly between The enrichment of miRNA targeting sites increased further for those genes with differential expression values in the top 20% and even further for those in the top 10%.…”
Section: Discussionmentioning
confidence: 99%
“…We first analyzed the AS tags with a focus on their differential expression in libraries representing cancerous and normal tissue samples. Previous studies have shown that the ratio of sense to antisense transcripts changes between normal and malignant tissue samples , and that antisense transcripts can be implicated in disease processes (Tufarelli et al 2003;Reis et al 2004). Our goal was to highlight the potential of the Tag-seq approach to identify known and novel antisense transcripts whose expression ratios changed significantly with respect to the sense gene, between normal and diseased states, between different stages of disease progression, or between cancer subtypes.…”
Section: Sense-antisense Transcripts In Cancer Librariesmentioning
confidence: 99%
“…La même équipe de D.R. Higgs a donc poussé l'exploration de sa première publication afin de confirmer le diagnostic [8]. En précisant les limites de la délétion, on constate qu'elle ampute l'extrémité 3' du gène LUC7L, dont les trois derniers exons et la zone de polyadénylation sont délétés (Figure 1).…”
Section: Nouvelleunclassified